Diagnostic performance of host protein signatures as a triage test for active pulmonary TB [data] - Köppel, Lisa; Denkinger, Claudia M. (Universität, 2023)
The current four symptom screen recommended by the WHO is widely used as screen to initiate diagnostic testing for active pulmonary tuberculosis (TB), yet the performance is poor especially when TB prevalence is low. In contrast, more sensitive molecular tests are less suitable for placement at primary care level in low resource settings. In order to meet the WHO End TB targets new diagnostic approaches are urgently needed to find the missing undiagnosed cases. Proteomics-derived blood host biomarkers have been explored because protein detection technologies are suitable for the point-of-care setting and could meet cost targets. This study aimed to find a biomarker signature that fulfills WHO’s target product profile (TPP) for a TB screening. 12 blood-based protein biomarkers from three sample populations (Vietnam, Peru, South Africa) were analyzed individually and in combinations via advanced statistical methods and machine learning algorithms. The combination of I-309, SYWC and kallistatin showed the most promising results to discern active TB throughout the datasets meeting the TPP for a triage test in adults from two countries (Peru and South Africa). The top performing individual markers identified at the global level (I-309 and SYWC) were also among the best performing markers at country level in South Africa and Vietnam. This analysis clearly shows that a host protein biomarker assay is feasible in adults for certain geographical regions based on one or two biomarkers with a performance that meets minimal WHO TPP criteria.